Statistics at The Zoo. Issue 5 (29th September 2020) - Holmes, Lisa; Edwards, Katie; Moss, Andy; Tollington, Simon; Fowler, Anna; Hughes, David; Sudell, Maria
Abstract: At Chester Zoo, it is not only the keepers who are taking care of the animals. Statistical methods are used to promote animal welfare and to preserve and protect endangered species.